2011
DOI: 10.1209/0295-5075/93/37006
|View full text |Cite
|
Sign up to set email alerts
|

Change of the effective spin degeneracy in CeNi 9− x Cu x Ge 4 due to the interplay between Kondo and crystal field effects

Abstract: Elastic and inelastic neutron scattering experiments were carried out on the heavyfermion systems CeNi8.6Cu0.4Ge4 and CeNi8CuGe4 to study i) the influences of Ni/Cu substitution on the crystal field parameters and to identify ii) the driving forces of quantum criticality in CeNi9−xCuxGe4. The relevance of competing RKKY and Kondo interactions and changes of the crystal field parameters is discussed. The crystallographic site where the Ni replacement by copper atoms takes place is identified by neutron powder d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
3
3
0
Order By: Relevance
“…The quasi-elastic neutron data, thus, reveal that Ni/Cu substitution causes a significant reduction of the Kondo energy scale and also a reduction of the effective ground state degeneracy towards a doublet in the case of CeNi 8 CuGe 4 . The latter is also confirmed by inelastic neutron data measured recently with an incident neutron energy of E i = 20.5 meV at FRMII where an approximate CF scheme with doublets at ground state, 5 meV and 12 meV is observed for CeNi 8 CuGe 4 [16].…”
Section: supporting
confidence: 80%
“…The quasi-elastic neutron data, thus, reveal that Ni/Cu substitution causes a significant reduction of the Kondo energy scale and also a reduction of the effective ground state degeneracy towards a doublet in the case of CeNi 8 CuGe 4 . The latter is also confirmed by inelastic neutron data measured recently with an incident neutron energy of E i = 20.5 meV at FRMII where an approximate CF scheme with doublets at ground state, 5 meV and 12 meV is observed for CeNi 8 CuGe 4 [16].…”
Section: supporting
confidence: 80%
“…mm point symmetry, respectively) [12]. This result was later confirmed by neutron powder diffraction experiments and subsequent Rietveld refinements which revealed that "on average each fourth Ni atom at the 16k sites is substituted by copper" [15]. In case of the CeNi 9−x Fe x Ge 4 solid solution series, our calculations suggest that substitution occurs preferentially at the 16l sites.…”
Section: Electronic Structure Calculationssupporting
confidence: 67%
“…The latter observation is counter-intuitive in the framework of the standard Doniach picture [14]. These results clearly suggest that it is rather the reduction of the effective spin degeneracy N [12,15] away from the paramagnetic quasi-quartet ground state in CeNi 9 Ge 4 which controls the formation of AF order in both systems. To gain further inside, whether (i) the interplay between Kondo effect and RKKY interaction or (ii) a change of the effective spin degeneracy is the most relevant control parameter in fine-tuning the CeNi 9−x T x Ge 4 systems (T: Co, Cu), we performed specific heat studies of CeNi 9−x Fe x Ge 4 (x ≤ 1).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Coleman pointed out that a large effective spin degeneracy N tends to stabilize the Kondo lattice ground state relative to a magnetically ordered one [6]. This means that, apart from the common tuning parameters such as (i) hydrostatic pressure [7], (ii) chemical pressure [8], or (iii) external magnetic field [9], also the change in effective spin degeneracy N by shifting the CF levels on an energy scale comparable to the Kondo energy might enforce a system towards a quantum critical point (QCP), as recently reported for CeNi 9−x Cu x Ge 4 [5,10,11]. This series of solid solutions represents a first benchmark system where a substitution driven quantum phase transition is not only linked with the changes of the relative strength of the Kondo effect and RKKY interaction, but also with a reduction of the effective crystal field ground state degeneracy.…”
Section: Introductionmentioning
confidence: 86%